Improving QoS by employing multiple physical NoCs on MPSoCs - Silva, Douglas Roberto Guarani da (2016)
Embedded systems adopt NoC-based MPSoCs since a large number of processing elements (PEs) enables the simultaneous execution of several applications, where some of these applications require real-time (RT) constraints. PEs communicate using messages in distributed memory MPSoCs. These messages can be classified as application messages, being the data generated by the applications, and management messages, used to ensure the correct operation of the platform. As the communication has a large impact on the application performance, an important concern in the design of MPSoCs is to improve the performance of the applications’ communication, particularly for RT applications. Two possible methods to optimize the communication performance includes: (i) prioritize the RT application messages over the messages generated by best-effort (BE) applications; (ii) isolate the application messages from the management messages, considering that complex MPSoCs require a large number of management services to meet the performance constraints. The NoC literature contains several works that differentiate traffic classes, proposing the isolation of these traffic classes by the use of multiple physical (MP) NoCs, reducing interferences among the flows belonging to different classes. The main goal of this work is to propose and to evaluate MP NoCs, with one network dedicated to the application messages and a second network for the management messages (MNoC). Based on the evaluation of the impact of the management traffic in the overall NoC communication, two different versions of M-NoCs are implemented and evaluated. Another important consideration for RT applications is to ensure that these applications meet their deadlines. The execution of these applications must have higher priority over the BE applications by dedicating more processing resources using a specialized RT scheduler. This work presents and evaluates an MPSoC platform capable of supporting both communication and computation QoS, being extensible for a large number of management services by to the use of MP NoCs. Results show that M-NoCs may be customized to have a small area overhead. The adoption of M-NoCs improves the communication performance, latency and jitter, even when the network used in the platform has QoS mechanisms (e.g. priority flows and circuit switching), by isolating the management traffic from the application traffic.